Faktor Penyebab Timbulnya Kepatuhan Masyarakat Terhadap Hukum (Legal Obedience) - Tauratiya, Tauratiya (ASY SYAR'IYYAH: JURNAL ILMU SYARI'AH DAN PERBANKAN ISLAM, 2018)
This study aims to determine the factors causing the emergence of public compliance with the law, through studies and analysis of a variety of literature both print and from various other social media. Community compliance with the law can essentially be interpreted as loyalty from the community as a legal subject that is realized through actions or behaviors that comply with existing law.Based on the results of the study, the authors conclude that there are two factors causing the emergence of community compliance with the law, namely internal and external factors. Internal factors are encouragement from within an individual that makes him obey the law without coercion from any party. Internal factors can be in the form of an individual's awareness of the benefits of the law, the belief that the law is made to realize a common goal, and other things that arise from the individual. While external factors can be interpreted as factors that encourage individuals to comply with laws that come from outside the individual self. External factors can include rewards, coercion, threats and other things that come from outside the individual.